Developing Contextual Design Principles for Enhancing 21st-Century Skills Amongst Early School Leavers - Matthews, Robert (Trinity College Dublin. School of Education. Discipline of Education, 2026)
Early school leaving poses substantial educational, social, and economic challenges. Early leavers often experience persistent unemployment, low income, insecure work, and social exclusion. Programmes such as Youthreach provide valuable support, yet research highlights a persistent deficit in 21st century skills; critical thinking, communication, collaboration, problem-solving, and technological competence, that are viewed as vital for young people to thrive in modern economies. These skills are increasingly demanded by employers and are central to the global education discourse, yet their development among early school leavers remains insufficiently addressed in both policy and practice. Considering the centrality of `employability' in compensation measures, such inattention constitutes a notable omission. Implemented in Ireland's Youthreach programme in Donegal, this study adopted a design-based research methodology, aligned with Article 12 of the UNCRC to ensure meaningful student voice participation. The research progressed through four iterative phases: analysis, design, implementation, and reflection, each informed by preceding findings and refined through collaboration with tutors and a Student Research Advisory Group. The findings of this research demonstrate that intentionally designed, collaborative, and technology-mediated learning experiences can meaningfully enhance early school leavers' confidence and engagement across multiple 21st-century skill domains. Participants reported increased capacity to work with others, communicate ideas, and engage in problem-solving tasks, alongside greater confidence in using digital tools for learning. These outcomes indicate that pedagogical design, rather than learner disposition, is a critical lever for skills development among marginalised youth, challenging deficit-oriented assumptions that have historically shaped responses to early school leaving. A key implication of the study is the importance of embedding learner voice and relational trust within pedagogical design. The co-construction of learning scenarios with tutors and young people fostered a sense of ownership, relevance, and legitimacy, contributing to sustained engagement and positive learning identities. A core contribution to knowledge is the formulation of a set of empirically informed design principles, iteratively refined through tutor and learner feedback, that extend the applicability of rights-based, collaborative pedagogical models to comparable educational contexts. These principles offer a transferable framework for practitioners and policymakers seeking to address equity, engagement, and skills development in analogous learning environments. More broadly, the findings underscore the need to move beyond compensatory models of provision towards pedagogical approaches that recognise early school leavers as adaptable learners and position skills development as central to the vocational focus of such programmes.
APPROVED